Establishment of Natural Mangrove Mud Crab Hatchery in Bangladesh, and Its Effectiveness with Dietary Lacto-sacc (Immunostimulant) on Mud Crab Reproduction, Nutritional Digestibility, and Health Status - Md. Abdul, Hannan (Elsevier Ltd., 2024)
The current study focused on establishment of mangrove based natural mud crab hatchery and assessment of different doses of dietary Lacto-sacc on mud crabs in the hatchery. The mated female crab samples were collected from the Sundarbans region and randomly divided into T1 (0 % Lacto-sacc), T2 (1 % Lacto-sacc), and T3 (1.5 % Lacto-sacc) treatments. The crabs were identified as Scylla olivacea species through morphometric and molecular techniques. The heavy metals toxicity was determined and observed highest quantity of heavy metals in soil sediments followed by water and crabs. The Lacto-sacc diet was prepared manually contains 45 % protein, 12 % lipid, 40 % carbohydrate, 3 % ash and live microorganisms Lactobacillus acidophilus (1.2×108 cfu/g), Enterococcus faecium (7.3×107 cfu/g), and Saccharomyces cerevisiae (2.7×109 cells/g). The highest survival was obtained 10.53±1.56 a % in first trail at 26 ‰ and increased to 12.15±1.58 a % after application of 1.5% Lacto-sacc (T3). Breeding activities was performed in controlled condition and zoea were transferred to mangrove pens. The rotifer (Brachionus plicatilis) and Artemia franciscana were used to feed the zoea whereas the rotifer enriched with the Tetraselmis suecica, Nannochloropsis oculate and S. cerevisiae. The metamorphosis stages of zoea were passed in the mangrove pens and turned up to crablets (0.027±0.005 g) stages after 28 days. The cannibalism % of crablets was observed 71.20±2.08 tested after crossing the crablet stages. The immune parameters of Lacto-sacc challenged mud crabs were tested at 0, 4, 8, and 12 weeks of sampling. After 12 weeks the total hemocyte count was increased in T3 treatment that was 30.17 % higher than control (T1). The hemolymph clotting time and superoxide dismutase (SOD) enzymes activities were also increased in T3 treatment but not significantly different among the treatments. The enzyme phenoloxidase (PO) and prophenoloxidase (proPO) were increased in T3 treatment that was significantly different (P<0.05) among the treatments. The value of PO was 0.022±0.006b, 0.076±0.077b, 0.165±0.023a (unit/g) and the value of proPO was 0.031±0.032b, 0.040±0.016b, 0.121±0.014a (unit/g) for T1, T2 and T3 respectively. The challenge test of hatchery produced crablets was performed in In Vivo condition in which 1.5% Lacto-sacc enriched crablets (T3) obtained highest survival (61.67±2.89a %). Moreover, the digestive enzyme activity was observed 3581.09±758.69b, 2762.67±582.76ab, 6090.67±2386.91a unit/g for protease, and 249.33±103.87b, 453.33±207.74ab, 634.67±103.87a unit/g for lipase for the treatment T1, T2, and T3 respectively whereas no significant difference was observed for amylase enzyme. In addition, the transverse section of the mud crab hepatopancreas and gut indicates a significant difference among the treatments in terms of their structure and cells count. The analysis of next generation sequencing of Lacto-sacc challenged mud crab also implies the higher number of microbes in T3 followed by T2 and T1 treatments. Finally, it’s concluded that 1.5 % Lacto-sacc (T3) performed best which increases the strong immunity of brood crabs and crablets to fight against disease infestation and increases the higher survival rates.